An interdisciplinary practice between Mathematics and Geography in Integrated Technical High School: construction of imaginary countries (Research, Society and Development, 2020)
This work aims to define an intervention carried out with a 3rd grade of Technical in Maintenance and Support in Informatics Integrated to High School of the Campus of São Vicente do Sul, from Federal Institute of Education, Science and Technology Farroupilha. It is an experience report that consisted of the construction of imaginary countries, focusing on geographic and mathematical concepts. The methodology used was didactic intervention and involves: guidance from students, reports, lecture, seminar presentations and elaboration of videos. The results found with this experience indicate that the methodology of orientation of the groups was fundamental to evaluate the learning progress of the students, even encouraged the dialogue between them. Therefore, the contents of Geography and Mathematics addressed activities, allowed important discussions, enable students to reflect on current themes present in their daily lives. It emphasizes the needed for an adequate infrastructure to carry out interdisciplinary activities, as well as a curriculum understanding that turn them possible. Although punctual, an activity promotes situations that require a critical positioning of students on the geographic spaces of the built countries.